NATIONAL AND INTERNATIONAL COOPERATION ON THE PREVENTION AND ERADICATION OF MONEY LAUNDERING - Husein, Yunus (Indonesian Journal of International Law, 2013)
The Prevention and eradication of money laundering, as one of the new paradigm in the effort of combating crimes, has its own mechanism in conducting both national and international cooperation, especially in relation to the cooperation of information exchange. The cooperation is mediated by the establishment of Memorandum of Understanding, and can also be conducted by the principle of reciprocity among parties. In its practice, the cooperation will strengthen the performance of Indonesian Financial Transaction Report and Analysis Center (INTRAC/PPATK) in conducting its duties and authorities as Financial Intelligence Unit.